Assessment of the level of state support for the agrarian sector in Russia and the European Union - D. M. Cherepanova; Yu. N. Nikulina; R. G. Yanbykh (Аграрная наука Евро-Северо-Востока)
The article provides the research of the state support for agriculture in Russia using the methodology of the Organization for Economic Cooperation and Development (OECD). The overall estimation of support for agricultural producers in Russia, considering not only budget transfers but also price support in 2020 amounted to 749 billion rubles or 12 % of gross revenue. At the same time, budgetary transfers account for 31.9 %. A significant amount is accounted for by the support of the market price, which is estimated through the difference between domestic and reference prices (prices "at the border") by the types of agricultural products. In the case of Russia, pork, poultry and beef producers received more than 655 billion rubles in 2020 as a result of price support. On the contrary, hidden taxation is typical for crop producers; about 308 billion rubles were withdrawn from them because of the pricing policy. However, the high overall market price support for agricultural producers in Russia in 2020 suggests that transfers from consumers exceed transfers in the form of subsidies. For comparison, price support in Russia and the EU on average for 2013-2020 was 44 % and 17 %, respectively. It is shown that in the EU 75% of the total support for agriculture is provided through the least market-distorting forms (support for general services, creation of state reserves to ensure food security), in Russia – 27 %. From the point of view of the sustainability of agriculture, the measures to support general services (infrastructure, science and education, innovation support) have the greatest impact on the volume of gross value added of the industry in Russia. The correlation coefficient for this type of support is the highest - 0.93, while the coefficient of determination is high – 86 %. This leads to the main recommendation on the adjustment of the agrarian budget in favor of supporting general services, which, in addition to the high positive effect on agricultural production, refers to least market-distorting measures and does not have the disadvantage of unequal access to agricultural producers, in contrast to, for example, direct subsidies and concessional loans.